2000
DOI: 10.1007/s007840000090
|View full text |Cite
|
Sign up to set email alerts
|

An attempt to explain why Tanzanian children drinking water containing 0.2 or 3.6 mg fluoride per liter exhibit a similar level of dental fluorosis

Abstract: The aim of this study was to identify factors that might explain the similar level of prevalence and severity of dental fluorosis in two neighboring areas in Tanzania: Kibosho; 0.2 mg fluoride/l, n = 96 and Arusha; 3.6 mg fluoride/l in drinking water, n = 80. Subjects aged 8-16 years were examined for dental fluorosis using the Thylstrup and Fejerskov Index (TFI). Based on the score on the upper left central incisor, the prevalence was not significantly different between the communities (TFI > or = 1). The sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…It might be speculated if the intake of calcium and/or vitamin D has been marginal or deficient in these populations. This would result in insufficient calcification of the osteoid [29,30]. It has been reported that workers with such exposure had better dental status than populations without fluoride exposure, although exposed young children may suffer from mottled teeth [25,30].…”
Section: Toxic Reactionsmentioning
confidence: 99%
“…It might be speculated if the intake of calcium and/or vitamin D has been marginal or deficient in these populations. This would result in insufficient calcification of the osteoid [29,30]. It has been reported that workers with such exposure had better dental status than populations without fluoride exposure, although exposed young children may suffer from mottled teeth [25,30].…”
Section: Toxic Reactionsmentioning
confidence: 99%
“…Children from two areas in the municipality of Arusha (Arusha and Arusha Meru) and from Moshi and Kibosho in the Kilimanjaro region were examined. Arusha town has approximately 135,000 inhabitants and is served by a municipal water supply containing 3.6 mg F/l in the drinking water [1,3,34]. Subjects from Arusha Meru are mostly ethnic Asians, while the inhabitants in Arusha and in both districts of the Kilimanjaro region are of African extraction.…”
Section: Methodsmentioning
confidence: 99%
“…The corresponding median scores in the high-F area were 5.0 in Arusha and 3.0 in Arusha Meru, i.e., with a significantly different distribution (P<0.001, Mann-Whitney U test). The findings related to dental fluorosis have been reported previously [1,2,3]. Re-examination for carious lesions was carried out on the lower right first molars in 32 children after 1 week.…”
Section: Clinical Examinationmentioning
confidence: 98%
See 2 more Smart Citations